MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS DASAR MELALUI KEGIATAN ENGLISH CAMP - ridho kurniawan; Yahfenel Evi Fussalam (LPPM Universitas Muhammadiyah Muara Bungo, 2020)
This study aims to improve the English speaking skills of STKIP MB students majoring in elementary school teacher education who take English courses, especially speaking skills at the basic level through English camp activities. English camp activities are outdoor activities carried out as practical speaking activities outside the classroom. . This activity is carried out after the lecture enters the midterm exam where students have first learned the basic theory for seven meetings at the beginning of the lecture. This research is a classroom action research conducted in two cycles with each cycle consisting of two meetings of English camp activities. The results of this study show their speaking ability at the basic level with the topics that have been determined increases significantly each meeting and at the end of each cycle taken from the speaking ability data with categories of assessment of topic accuracy, use of vocabulary, pronunciation and fluency in speaking. . The conclusion in the study shows that English camp activities can improve basic level speaking skills for PGSD STKIP MB students with success indicators of 80% of students getting an oral speaking exam score of 75 or more